2017
DOI: 10.1007/s12020-017-1458-3
|View full text |Cite
|
Sign up to set email alerts
|

Microsurgical therapy of pituitary adenomas

Abstract: In experienced hands, transsphenoidal microsurgery for PAs achieves remission in most patients with a low complication rate. Pituitary function is preserved in most cases and can recover in more than one-third of patients with preoperative hypopituitarism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
44
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 51 publications
1
44
0
7
Order By: Relevance
“…Postoperative permanent DI is relatively rare in patients with pituitary adenoma [ 14 ]. Mortini et al [ 16 ] reported that permanent DI occurred in 0.9% of patients. Permanent DI occurs when there is loss of 85% or more of the hypothalamic magnocellular neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative permanent DI is relatively rare in patients with pituitary adenoma [ 14 ]. Mortini et al [ 16 ] reported that permanent DI occurred in 0.9% of patients. Permanent DI occurs when there is loss of 85% or more of the hypothalamic magnocellular neurons.…”
Section: Discussionmentioning
confidence: 99%
“…The data presented convincingly show, which excellent results can be achieved with a microsurgical technique by an experienced surgeon in a specialized center with a high case load. Moreover, even the rare entities of pituitary adenomas, such as thyrotropinomas, are represented in impressive numbers [1]. The data furthermore show that adaption of the endoscopic method is not necessarily required, that in contrast, impressive results can be obtained by using microsurgical excellency and that microsurgery is not at all outdated in the therapy of pituitary tumors.…”
mentioning
confidence: 85%
“…In this article [1], Mortini et al review their extensive experience with the surgical treatment of pituitary adenomas. Their results, in terms of tumor resection and normalization rates of hormonal oversecretion are outstanding, while the complication rate is minimal.…”
mentioning
confidence: 99%
“…This framework differs from the traditional model of pharmacological trials to accommodate the distinct way surgical developments occur, particularly since individual operator skill and technique modifications at the early stages can differentially impact outcomes. [ 46 ]. A subsequent paper introduced Stage 0, a preclinical stage, for testing involving cadavers, animals, or simulations, while another clarified the use of the IDEAL framework in surgical device development [ 25 , 56 ].…”
Section: Introductionmentioning
confidence: 99%